Evaluating the utility of pest control sourced rats for zoonotic pathogen surveillance. (6th March 2022) - Robinson, Sarah J.; Finer, Rachel; Himsworth, Chelsea G.; Pearl, David L.; Rousseau, Joyce; Weese, J. Scott; Lindsay, L. Robbin; Dibernardo, Antonia; Huynh, Chris; Jardine, Claire M.
Abstract: Norway rats ( Rattus norvegicus ) inhabit cities worldwide and live in close association with humans. Studies of urban rat zoonoses often rely on live‐trapping, with fewer studies using rats sourced through lethal pest control interventions. Our objectives were to evaluate the utility of rats collected by pest control professionals for zoonotic pathogen surveillance and determine whether we could detect Leptospira interrogans and Streptobacillus moniliformis in pest control sourced rats. Rat carcasses were submitted from Windsor, Canada by pest control professionals between November 2018 and March 2020. Submissions were categorized by season and land use. Necropsies were performed to classify carcass quality, collect tissue samples, and record demographic data. The association between carcass quality and the ability to collect tissue samples for pathogen surveillance was assessed via an exact logistic regression model. Using PCR, a subset of kidney and spleen samples were tested for L .  interrogans and S. moniliformis, respectively. Our sample of pest control sourced rats had similar sex and age distributions to those of live‐trapping studies. Rats were primarily submitted from residential and industrial locations during fall, winter, and spring, which may reflect pest control service areas and peak business periods, rather than rat distribution. Of 124 submissions, 98 (79.0%) of rats showed only mild decomposition. The odds of collecting all tissue samples were reduced for fair compared to good‐quality carcasses (OR: 0.029; 95% CI: 0–0.25; p  = .0009) and for poor compared to fair‐quality carcasses (OR: 0.048; 95% CI: 0.00085–0.53; p  = .0065). Leptospira interrogans and S. moniliformis were detected in 9.1% (4/44) and 27.3% (15/55) of a subset of rats tested, respectively. Our results suggest that pest control sourced rats are suitable for surveillance for multiple zoonotic pathogens in urban environments. This method of rat collection may provide preliminary information to guide more detailed ecological studies.